Comparison of xpert MTB/RIF assay, line probe assay, and culture in diagnosis of pulmonary tuberculosis on bronchoscopic specimen - Swapna Kanade; Zakiuddin Mohammed; Anisha Kulkarni; Gita Nataraj (International Journal of Mycobacteriology, 2023)
Background: In patients unable to expectorate good quality sputum or with minimal to none sputum production, bronchoscopic specimens may be collected. The objective of the study is to determine the use of Xpert MTB/RIF assay and line probe assay (LPA) in the diagnosis of pulmonary TB (PTB) using specimens collected by bronchoscopy in a tertiary care center. Methods: Bronchoscopy specimens received in the TB laboratory were processed by microscopy, Xpert MTB/RIF assay, LPA, and mycobacteria growth indicator tube (MGIT) culture. Results of MGIT culture are considered gold standard. Results: Of the 173 specimens tested, MTB was detected in 48 (27.74%) samples by any of the above methods. Positivity in bronchoalveolar lavage was 31.4% (44/140) and in bronchial wash was 12.1% (4/33). Detection by microscopy, Xpert assay, and culture was 20 (11.56%), 45 (26.01%), and 38 (21.96%), respectively. Culture detected MTB in three additional specimens compared to Xpert assay. Xpert assay detected MTB in 45 (26%) specimens which include 10 specimens which were negative by culture. LPA detected MTB in 18 (90%) out of 20 smear-positive specimens. RIF resistance was detected in 20 (41.7%) specimens by Xpert and/or MGIT culture drug susceptibility testing (DST). Isoniazid (INH) resistance was detected in 19 specimens by LPA and MGIT culture DST. Conclusion: Bronchoscopy can provide alternative respiratory specimens for diagnosing PTB in patients with difficulty to expectorate sputum. The utility of Xpert MTB/RIF as a rapid, sensitive, and specific test should always be supplemented with culture in difficult-to-obtain and precious respiratory specimens. LPA plays an important role in rapid detection of INH monoresistance.